Procedings of the British Machine Vision Conference 1994 1994
DOI: 10.5244/c.8.39
|View full text |Cite
|
Sign up to set email alerts
|

A Non-linear Generalisation of PDMs using Polynomial Regression

Abstract: We have previously described how to model shape variability by means of point distribution models (TDMs,) in which there is a linear relationship between a set of shape parameters and the positions of points on the shape. This linear formulation can fail for shapes which articulate or bend.' we show examples of such failure for both real and synthetic classes of shape. A new, more general formulation for PDMs, based on polynomial regression, is presented. The resulting Polynomial Regression PDMs (PRPDMsj perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…1 are examples from a synthetic class of shapes. We have previously described in detail how they are generated [2]. Training a linear PDM on 200 tadpoles, we found that three modes of variation were needed to explain 95% of the variance in the training data [2].…”
Section: Tadpole Datamentioning
confidence: 96%
See 3 more Smart Citations
“…1 are examples from a synthetic class of shapes. We have previously described in detail how they are generated [2]. Training a linear PDM on 200 tadpoles, we found that three modes of variation were needed to explain 95% of the variance in the training data [2].…”
Section: Tadpole Datamentioning
confidence: 96%
“…We have recently described [2] a modified class of models known as a Polynomial Regression PDM (PRPDM). The approach is motivated by noting that the eigen-analysis used to extract the modes of variation for a standard PDM can be conceptualised (however implemented) as a process of sequentially fitting modes.…”
Section: The Polynomial Regression Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensions to cover non-rigid shape deformations involved using a single global shape model in combination with nonlinear PCA techniques [25,26] or a probabilistic model [4], as well as the use of multiple local-linear shape models [7,11]. Other work considered joint linear shape and texture models [3,6,15] to capture underlying dependencies in a principled way.…”
Section: Previous Workmentioning
confidence: 99%